A case of epigastric pain one day after normal vaginal delivery. (18th April 2012) - Lo, TK; Chan, LL; Lau, WL; Wong, SH; Wong, M; Lo, KY; Leung, WC
Abstract : A 31-year-old primiparous women with haemoglobin H disease complained of epigastric pain one day after giving uneventful vaginal birth to a 2.0kg boy at 38 weeks. Epigastric pain temporarily settled with oral antacid, she became dizzy and sweaty associated with back pain. She was pale and hypotensive, abdomen distended. Ultrasound showed free fluid inside the abdomen. Diagnostic tapping yielded blood. Haemoglobin was 6.4g/dl. Emergency laparotomy was performed. Splenomegaly (20cm in span) with rupture and 2.5L hemoperitoneum was found. Splenectomy was done. The total blood loss was 3.5L. Seven units of pack cells and 4 units of fresh frozen plasma were transfused. Histology showed congestive splenomegaly (605gm). Further investigations showed normal G6PD activity, negative blood smears for malaria parasites, normal red cell morphology and negative monospot test. This is the first report of postpartum splenic rupture related to thalassemic splenomegaly.